Climate‐driven tree mortality: insights from the piñon pine die‐off in the United States. Issue 2 (18th September 2013) - Hicke, Jeffrey A.; Zeppel, Melanie J. B.
<x xml:space="preserve">Abstract</x> Featured paper: See also the Editorial by McDowell et al